Charge Density Waves and Magnetism in Topological Semimetal Candidates GdSbxTe2−x−δ. Issue 10 (1st July 2019) - Lei, Shiming; Duppel, Viola; Lippmann, Judith M.; Nuss, Jürgen; Lotsch, Bettina V.; Schoop, Leslie M.
Abstract: Many topological semimetals are known to exhibit exceptional electronic properties, which are the fundamental basis for design of novel devices and further applications. Materials containing the structural motif of a square net are known to frequently be topological semimetals. In this work, the synthesis and structural characterization of the square‐net‐based magnetic topological semimetal candidates GdSb x Te2− x − δ (0 ≤ x ≤ 1, δ indicating the vacancy level) are reported. The structural evolution of the series with Sb substitution is studied, finding a transition between a simple tetragonal square‐net structure to complex superstructure formations due to the presence of charge density waves. The structural modulations coincide with a significant modification of the magnetic order. This work thus establishes GdSb x Te2− x − δ as a platform to study the interplay between crystal symmetry, band filling, charge density wave, and magnetism in a topological semimetal candidate. Abstract : The magnetic topological semimetal candidate GdSbTe is shown to exist in off‐stoichiometric compositions that induce structural distortions, including incommensurate charge density waves. The authors report the structural evolution of the series GdSb x Te2− x − δ as well as their magnetic properties. The GdSb x Te2− x − δ system provides a nice platform to study the interplay between charge density waves, magnetism and topological band structures.